(untitled) (Research, Society and Development, 2020)
The main challenge encountered in agriculture today is to produce a healthy food for a growing population that is increasingly concerned with the health and food they are consuming, thus opting for organic foods because they have a high nutritional value and food safety. Banana is the second most consumed fruit in the world for its easy access, and when introduced into the organic system, the value of the crop is added. The objective of this work was to show the ways of production of ’Prata Anã’ banana with organic fertilization, showing the benefits, management, productivity and other details regarding the production and conservation of the environment. This work had as the research method used, the descriptive one, where the techniques of data collection in articles, books, theses and dissertations were used. Thus, there are practices, such as organic agriculture, that contribute to reducing the impacts produced by the use of pesticides. By making use of organic fertilizer the soil becomes more productive and fertile, increasing its biodiversity and improving the quality of the food produced. With the production of organic banana, it is desired that the producer has a distinct market with a differentiated product, being environmentally friendly, economically viable and socially fair. This paper aims to show the processes for the implementation of a banana plant, in order to help instruct potential stakeholders.